دراسة تحليلية لواقع نقل الركاب البرّي في سورية (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول البحث موضوع النقل البري للركاب في سورية بشقيه الطرقي والسككي, ويتعرض بالدراسة لأهم العوامل المؤثرة في هذا القطاع الحيوي والمهم من قطاعات النقل. في محاولة لإلقاء الضوء على مدى تطور وتفاعل العناصر الضرورية لتقديم خدمات نقل مميزة. مبيناً بالأرقام واقع هذه العناصر ومراحل تطورها في مختلف محافظات القطر. مع عرض لواقع مؤسسات القطاع العام العاملة في مجال نقل الركاب الطرقي, ودراسة العلاقة بين النقل الطرقي والنقل السككي لإظهار مدى التكامل والتفاعل بينهما, أو المنافسة في تلبية حاجات ومتطلبات السكان في مجال نقل الركاب. ثم تقدم دراسة للعلاقة الارتباطية بين عناصر نقل الركاب البري في سورية ببعضهما بعض, وذلك من خلال رصد تطور هذه العناصر خلال عدة سنوات ماضية, وحساب معاملات الارتباط لقيم جميع العناصر. وفي النهاية نقدم ملخصاً لأهم النتائج التي تم الوصول إليها من خلال الدراسة السابقة مع عرض لبعض المقترحات والتوصيات.   This research studies land transportation of people in Syria both by roads and rails, focusing on the most important factors in this vital and important sector. We concentrate on the extent of development and interaction of necessary elements to offer distinguished transportation services. We also clarify the situation of the services in Syrian governorates, using figures. We present the situation of the institutions of the public sector working in the field of the public transport, and we study the relation between road transport and rail transport to show the interaction or competition between them in satisfying the needs of people in the field of public transportation. We then study the relationship between the elements of land public transportation in Syria, observing the development of these elements over the past years, and calculating the correlation between these elements. Finally, we present a summary of the most prominent results and put forward some suggestions and recommendations.